2018
DOI: 10.5152/dir.2018.17450
|View full text |Cite
|
Sign up to set email alerts
|

Size-specific dose estimates in chest, abdomen, and pelvis CT examinations of pediatric patients

Abstract: In pediatric CT exams involving CAP region, CTDIvol and the water equivalent diameter at the middle of the scan range can be used to provide a reasonable estimate of mean SSDE with an RMSD of 11% at most.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…showed that the center-slice method results in a mean relative absolute error of 2–5% in pediatric and adult abdominal and chest CT compared with the slice-by-slice method ( 14 ) . For pediatric thoracic, abdominal and pelvic scans, Öszoykal et al determined a root-mean-squared error of 1.2–11% when comparing the \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathrm{SSDE}$\end{document} from the center-slice method with the slice-by-slice determination ( 26 ) . Furthermore, \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathrm{SSDE}$\end{document} also depends on the positioning of the patient in the isocenter of the scanner gantry, which can lead to inaccuracies if performed incorrectly ( 7 , 27 , 28 ) .…”
Section: Discussionmentioning
confidence: 99%
“…showed that the center-slice method results in a mean relative absolute error of 2–5% in pediatric and adult abdominal and chest CT compared with the slice-by-slice method ( 14 ) . For pediatric thoracic, abdominal and pelvic scans, Öszoykal et al determined a root-mean-squared error of 1.2–11% when comparing the \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathrm{SSDE}$\end{document} from the center-slice method with the slice-by-slice determination ( 26 ) . Furthermore, \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\mathrm{SSDE}$\end{document} also depends on the positioning of the patient in the isocenter of the scanner gantry, which can lead to inaccuracies if performed incorrectly ( 7 , 27 , 28 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies (16)(17)(18) proposed fully automated methods. Özsoykal et al (19) proposed an automated patient contour after the exclusion of irrelevant objects such as clothes and the CT table from the image. The threshold value was determined through trial and error until a complete successful segmentation of the body contour was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…20 An accurate automated approach to finding D w , in order to obtain accurate patient dose, is in great demand. [24][25][26][27][28][29][30] Anam et al 25 proposed a fully automated method to calculate D w in a phantom and in human anatomic regions using a region of interest (ROI) automatically fitted to the patient border. The automated calculation produced an excellent correlation to the manual calculation (R 2 = 0.999).…”
Section: Introductionmentioning
confidence: 99%
“…The automated calculation produced an excellent correlation to the manual calculation (R 2 = 0.999). Özsoykal et al 26 designed a patient contour upon the exclusion of irrelevant objects such as the CT table or clothes from the original image. The threshold value was then determined via trial and error until a complete segmentation of the body contour F I G U R E 2 Flowchart of the proposed algorithm was achieved.…”
Section: Introductionmentioning
confidence: 99%